Cognitive, Neuroanatomical, and Genetic Predictors of Executive Function in Healthy Children and Adolescents. Issue 7 (3rd October 2018) - Pan, Jessica; Sawyer, Kayle; McDonough, EmilyKate; Slotpole, Laura; Gansler, David
ABSTRACT: The Dimensional Change Card Sort (DCCS) is a measure of cognitive flexibility for children, which requires rule-use and shifting. Demographic, cognitive, regional cortical thickness, and genetic variables, including those related to language and executive function, were used to build predictive models of DCCS scores in 556 healthy pediatric participants. Gender, age, frontal, and temporal lobe regions of interest, and measures of sustained attention, inhibition, and word reading were selected as the best predictors of DCCS performance. Results indicated that DCCS performance is related to a broad range of cognitive functions and anatomic regions associated with various levels of cognitive function.